Practical training report: Padawan Municipal Council / Evelyn Pirit - Pirit, Evelyn (University Technology MARA Sarawak, 2013)
The Padawan Municipal Council formerly known as Kuching Rural District Council was formed at the end of 1956 under the provisions of the Local Authority Ordinance 1948, Chapter 117. The location ofthe council office is at Kota Padawan, 10th Mile, Jalan Penrissen, Kuching. The history of the appointment of the chairman is different. In 1957 to 1961, the chairman ofthe council was the District Officer;this was in the Era of Colonialism. Then, the chairman was elected during government election for the period of 1962 to 1981. Starting in November 1981 until present, the chairman is appointed.